Reinfections and rotavirus serotypes in Belém, Brazil - Alexandre da C. Linhares; Yvone B. Gabbay; Ronaldo B. de Freitas; Joana D'arc P. Mascarenhas (Revista do Instituto de Medicina Tropical de São Paulo, 1988)
Repeated infections involving different rotavirus serotypes were detected in four children living in Belém, who were followed up since birth to three years of age. In one child (Reg. 23.983) three successive symptomatic infections (one of them associated with serotype 2) were noted: the first, at four months of age, the second at 20 months and the third at 27 months. Another child had two subsequent infections, the first one by rotavirus serotype 1, and the second by a not identified rotavirus serotype. In this case two episodes of rotavirus-related diarrhoea were recorded, occurring eight months apart. Apparent infections were detected on two occasions involving the same child (Reg. 24.004), the first being associated with serotype 1, and the second with serotype 2. The fourth child (Reg. 24.097) had two successive infections by not determined rotavirus serotypes, without clinical manifestations; the first occurred at 24 months and the second at 28 months.